Effectiveness of a program based on dialectical behavioral therapy to develop a positive self-view and reducing some symptoms of eating disorders for female university students in the Kingdom of Saudi Arabia - Mahboob, Hanan Mohammed Amin (Dirasat: Human and Social Sciences, 2024)
Objectives: The current study aimed to verify the effectiveness of a program based on behavioral dialectical therapy to develop a positive self-view and reduce some symptoms of eating disorders for female university students in the Kingdom of Saudi Arabia. Methodology: The study used the Positive Self-View Scale and the therapeutic program based on dialectical behavioral therapy (prepared by the researcher), and the Eating Disorders Scale prepared by Garner et al (1982). The study was applied to a sample of (16) female university students, who suffer from Eating disorders, divided into two groups (experimental and control), each group consisting of (8) female students. The study also followed the experimental method. Results: The results of the study indicated that there were statistically significant differences between the average scores of the experimental group in the pre- and post-measurements of positive self-view and eating disorders in favor of the post-application. there were also statistically significant differences between the average scores of the experimental group and the average scores of the control group in the post-measurement of both positive self-view and eating disorders, and the continued effectiveness of the program after completion of the application. Conclusion: The study recommended the need to pay attention to sports and recreational activities that reduce stress among female university students, and thus reduce eating disorders.